subtracting (2) from (1)
3y=3 and so y=1
substituting
3x+2=8
3x=6 and so x=2
the soluion set={2,1}
your solution is absolutely correct
2006-10-27 23:33:15
·
answer #1
·
answered by raj 7
·
0⤊
1⤋
Correct, but hard work, try:
3x - 2y = 8 minus
3x - y = 5
gives 3y = 3
y = 1
now substitute for y in either equation
3x - 1 = 5
3x = 5 + 1
x = 2
2006-10-28 12:53:03
·
answer #2
·
answered by ken c 1
·
0⤊
0⤋
you don't have to put 'a1' and 'a2'in you answer
"3x + 2y = 8
3x - y = 5
3x = 8 - 2y
x = (8-2y)/3
3(8-2y)/3 - y = 5
3(8-2y) - 3y = 15
24-6y - 3y = 15
-6y - 3y = 15 - 24
-9y = -9
y=1
x = (8-2)/3
x = 2"
your answer is correct
i hope that this helps
2006-10-28 07:13:57
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3x + 2y = 8- - - - -Equation 1
3x - y = 5 -- - - - -Equation 2
- - - - - - - - - - - - -
Multiplty equation 2 by 2
2(3x) - 2(y) = 2(5)
6x - 2y = 10 New Equation 2
- - - - - - - - - -
Elimination by addition Method
Elimination of the y variable
3x + 2y = 8
6x - 2y = 10
- - - - - - - -
9x = 18
9x/9 = 18/9
x = 2
The answer is x = 2
Insert the x value into equatiopn 2
- - - - - - - - - - - - - - - - -
Solving for y
3x - y = 5
3(2) - y = 5
6 - y = 5
6 - y - 6 = 5 - 6
- y = - 1
-1y/- 1 = -1/- 1
y = 1
The answer is y = 1
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - -
Check for equation 2
3x - y = 5
3(2) - (1) = 5
6 - 1 = 5
5 = 5
- - - - - - -
Check for equation 1
3x + 2y = 8
3(2) + 2(1) = 8
6 + 2 = 8
8 = 8
- - - - - - - - - - - - - - - - -
The solution set { 2, 1 }
- - - - - - - - - - - - - - - - - - -
Your answer is correct
The Elimination by addition method and the substitution method work.
2006-10-28 09:36:48
·
answer #4
·
answered by SAMUEL D 7
·
1⤊
0⤋
Focusing on the use of a1 and a2 in your worked example - which is what your question is really about - I shouldn't put them there.
The a1 and a2 serve to highlight
-9y = -9 and
y = 1
-9y = -9 is the thought process immediately preceding y =1.
I see no point in highlighting the thought process, which immediately precedes one of the solutions.
There may be a virtue in highlighting the solution. If there is a virtue in highlighting one solution, there is probably a virtue in highlighting the other (x = 2).
I have never seen these a1s and a2s used before and think their use in your answer is inconsistent.
I think the basic way of expressing the answer as
y = 1
x = 2
is clear and unambiguous.
I think the smartest way (for people who understand it) is
the solution set is {2,1}
as rfamilyme expressed it.
2006-10-28 16:59:51
·
answer #5
·
answered by rosie recipe 7
·
0⤊
0⤋
However, at the line beginning
3(8-2y)/3 -
instead of multiplying through by 3, you could just divide top and bottom of this fraction by 3 and get
8 - 2y - y = 5
thus making the working slightly simpler.
2006-10-28 06:41:11
·
answer #6
·
answered by Hy 7
·
0⤊
0⤋
Yes, but why not just go straight from
3(8-2y)/3 - y = 5
to
8 - 2y - y = 5
then
-3y = -3
y=1
2006-10-28 06:43:34
·
answer #7
·
answered by George D 4
·
0⤊
0⤋
Yep perfect!
2006-10-28 06:36:45
·
answer #8
·
answered by Wondergirl 2
·
0⤊
0⤋
That's perfect, your question doesn't make much sense!
2006-10-28 06:38:22
·
answer #9
·
answered by the man at your window 2
·
0⤊
0⤋